HIV-1 integrase inhibitors that compete with the target DNA substrate define a unique strand transfer conformation for integrase - Espeseth, Amy S. (The National Academy of Sciences, 2000)
Diketo acids such as L-731,988 are potent inhibitors of HIV-1 integrase that inhibit integration and viral replication in cells. These compounds exhibit the unique ability to inhibit the strand transfer activity of integrase in the absence of an effect on 3′ end processing. To understand the reasons for this distinct inhibitory profile, we developed a scintillation proximity assay that permits analysis of radiolabeled inhibitor binding and integrase function. High-affinity binding of L-731,988 is shown to require the assembly of a specific complex on the HIV-1 long terminal repeat. The interaction of L-731,988 with the complex and the efficacy of L-731,988 in strand transfer can be abrogated by the interaction with target substrates, suggesting competition between the inhibitor and the target DNA. The L-731,988 binding site and that of the target substrate are thus distinct from that of the donor substrate and are defined by a conformation of integrase that is only adopted after assembly with the viral end. These results elucidate the basis for diketo acid inhibition of strand transfer and have implications for integrase-directed HIV-1 drug discovery efforts.